Acting Right? Privatization, Encompassing Interests, and the Left. Issue 2 (11th May 2015) - Hicks, Timothy
Abstract : I present a theoretical account of the politics of privatization that predicts left-wing support for the policy is conditional on the proportionality of the electoral system. In contrast to accounts that see privatization as an inherently right-wing policy, I argue that, like trade policy, it has the feature of creating distributed benefits and concentrated costs. Less proportional electoral systems create incentives for the Left to be responsive to those who face the concentrated costs, and thus for them to oppose privatization more strongly. More proportional systems reduce these incentives and increase the extent to which distributed benefits are internalized by elected representatives. Hypotheses are derived from this theory at both the individual and macro-policy level, and then tested separately. Quantitative evidence on public opinion from the 1990s and privatization revenues from Western European countries over the period 1980–2005 supports the argument.